METODE TUTOR SEBAYA DALAM BELAJAR TARI DAERAH SETEMPAT PADA KEGIATAN PENGEMBANGAN DIRI - Frisilia Yulisianti; Indrayuda Indrayuda; Zora Iriani (SENDRATASIK UNP, 2012)
This articel purpose of to describe peer tutors method in learning local dance on the extracurricular at SMA Negeri 1 Lubuk Alung. Therefore, the researcher uses the method of descriptive qualitative research to describe this research. The data of this research is the development of student activity when the extracurricular project goes on. The source of this research is the direct observation that the researcher does herself. The data was collected by using observational student activity format and the documentation of students’ learning activity. The finding of this research is that the students understand the explanation that come from their peers rather than the explanation given by the teacher. Therefore, peer tutor is more effectively done in the learning processor traditional dance in SMA Negeri 1 Lubuk Alung. Kata kunci: metode tutor sebaya, belajar, tari daerah setempat, kegiatan pengembangan diri